Portuguese Version of the Ageing Attitudes Questionnaire (AAQ): Validation of the Psychometric Properties - Pedroso de Lima, Margarida (2022)
The Ageing Attitudes Questionnaire—AAQ was validated for the Portuguese population to understand the importance of attitudes towards old age and their impact on the subjective wellbeing of older adults. A sample of 400 subjects (from 18 to 93 years) answered a socio-demographic questionnaire, and the AAQ, composed of three subscales (psychosocial losses, physical change, and psychological growth). The CFA confirmed the tri-factorial structure with very good adjustment of the model to the data, with the Cronbach alpha of the total scale scoring 0.84 and ranging from 0.65 to 0.77 for each factor. A total of nine items were omitted for poor factor loadings (<0.50), namely in factor 1 items 9-17-20, in factor 2 items 7 and 24 and, finally, in factor 3 we omitted items 4-18-19-21. Notwithstanding, three items below the criteria were maintained, as they conceptually fit into the factor. Of the final 15 AAQ items, 5 belong to the Psychosocial Loss Factor, 6 to Physical Change Factor, and 4 to Psychosocial Growth Factor. This tree factor model explained 50.1% of the total variance. In conclusion, this study supports that AAQ has acceptable validity, confirming the composite reliability and the discriminant validity, but not the convergent validity. Through multigroup analysis, the invariance of the scale was confirmed. This validation is of pivotal importance once it allows measuring attitudes towards ageing in the Portuguese population, thus facilitating the prevention of ageism and the promotion of well-being across the lifespan.